Study on prevalence of hepatitis B in pregnant women and its effect on maternal and fetal outcome at tertiary care centre - Mishra, Sunita; Purandre, Priyali; Thakur, Ratna; Agrawal, Shweta; Alwani, Madhuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hepatitis-B is caused by double stranded DNA virus. Prevalence of hepatitis B in pregnant woman worldwide is 2.5 to 1.5% whereas in India it is 2 to 7.7%. Methods: This is a retrospective study conducted at SAMC and PGI, Indore between January 2016 to December 2016. Hepatitis- B prevalence and outcome was assessed by doing routine screening of hepatitis B antigen in our indoor patients and finding out their maternal and fetal outcome. Results: Total 3567 deliveries were conducted during study period, out of them 39 were diagnosed as HbsAg positive pregnant patient; so, prevalence was found to be 1.09%. out of these, 84.6% were booked cases, mode of delivery was vaginal in 66.67% cases, preterm Delivery was in 10.26% of cases, meconium stained liquor was found in 5.13% cases, maternal mortality was nil, perinatal mortality was found in 2.56% cases and 5.13% cases were admitted in NICU. Conclusions: Screening of all pregnant women for HbsAg irrespective of risk factors will definitely help to know the correct prevalence and reduce the transmission of hepatitis B infection. Hepatitis B is a major public health problem in India and will continue to be until appropriate nationwide vaccination programs and other control measures are established.